The largescaled terapon Terapon theraps : a new Indo‐Pacific fish in the Mediterranean Sea - L. Lipej; B. Mavrič; V. ŽIža; J. Dulčić (Journal of Fish Biology, 2008)
A specimen of the largescaled terapon Terapon theraps was recorded for the first time from the Mediterranean Sea. The finding of T. theraps in the northernmost part of the Mediterranean Sea raises the number of Lessepsian migrant species to at least 68 and in the Adriatic Sea to at least 11.